Chemical forms of heavy metals in bottom sediments of the Mitręga reservoir = Chemiczne formy metali ciężkich w osadach dennych zbiornika wodnego Mitręga - Dąbrowska, Lidia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Bottom sediments originating from the Mitręga water reservoir were studied. It was assayed, in what chemical forms heavy metals (zinc, copper, nickel, cadmium and lead) occur in sediments, using the method of sequential extraction BCR. According to the geochemical criteria with respect to the content of Zn, Cu and Ni, the sediments in all measuring points were classified as uncontaminated, however because of the Cd content - as moderately contaminated.
Keywords: osady denne; metale ciężkie; ekstrakcja sekwencyjna; mobilność; bottom sediments; heavy metals; sequential extraction; mobility